(untitled) (Journal of Medical Sciences, 2022)
Infections caused by drug-resistant bacteria are among the most common causes of death in the intensive care unit, and this study is conducted to investigate the contaminants of the intensive care unit (ICU) in the target hospital and to evaluate the efficacy of the most frequently used antibiotics. Using sterile swabs, twenty samples were taken from different places within the intensive care unit. Basic biochemical reactions were used to identify the isolated bacteria and the Phoenix 100 BD digital system technique was used to confirm the identification and to assess the sensitivity of the isolated bacteria against sixteen standard antibiotics belonging to different classes. Three different genera of the Gram-negative bacteria and one genus of the Gram-positive bacteria were found as contaminants inside the examined ICU, Enterobacter cloacae, Pasturella multocida, Acinetobacter baumannii, and Bacillus cereus. A diverse susceptibility of Enterobacter cloacae, Pasturella multocida has been shown in this study against tested antibiotics. However, Acinetobacter baumannii showed resistance to all tested antibiotics except for Colistin while Bacillus cereus bacteria showed the opposite as it was sensitive to all tested antibiotics except for Colistin. Conclusion: The targeted intensive care unit was contaminated with 4 types of pathogenic bacteria, including multi and pan-drug-resistant types, the issue which is considered a life-threatening risk factor for patients. The hospital management has been reported the results and the instructions were applied.